2000
DOI: 10.1016/s0022-3182(00)70504-8
|View full text |Cite
|
Sign up to set email alerts
|

Food Perceptions and Dietary Behavior of American-Indian Children, Their Caregivers, and Educators: Formative Assessment Findings from Pathways

Abstract: Dietary findings from a school-based obesity prevention project (Pathways) are reported for children from six different American-Indian nations. A formative assessment was undertaken with teachers, caregivers, and children from nine schools to design a culturally appropriate intervention, including classroom curriculum, food service, physical education, and family components. This assessment employed a combination of qualitative and quantitative methods (including direct observations, paired-child in-depth int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 37 publications
2
8
0
Order By: Relevance
“…Our results parallel those from recent studies in the US conducted by Gittelsohn et al 20 and Hertzler et al 21 Gittelsohn et al found that the three most commonly reported food rules practised by 24 interviewed teachers were: (i) to encourage children to finish their foods during the school meal, (ii) to wash hands, and (iii) to taste all foods. Hertzler et al found that children's food problems, according to the staff, were that they liked fast food and did not taste new foods.…”
Section: Teaching While Eating -The Pedagogic Mealsupporting
confidence: 89%
“…Our results parallel those from recent studies in the US conducted by Gittelsohn et al 20 and Hertzler et al 21 Gittelsohn et al found that the three most commonly reported food rules practised by 24 interviewed teachers were: (i) to encourage children to finish their foods during the school meal, (ii) to wash hands, and (iii) to taste all foods. Hertzler et al found that children's food problems, according to the staff, were that they liked fast food and did not taste new foods.…”
Section: Teaching While Eating -The Pedagogic Mealsupporting
confidence: 89%
“…The present study provides data that were not previously available with respect to the associations between psychosocial dietary factors and their potential impact on dietary behaviours amongst Inuit. Acquisition of unhealthy foods was on average more frequent than the acquisition of healthier alternatives, including traditional foods, and preparation methods that added fat were used most often, which were also found in studies of other Aboriginal North American populations (Gittelsohn et al. , 2000, 2006; Archer et al.…”
Section: Discussionsupporting
confidence: 56%
“…Rural residency alone presents a unique set of barriers to healthy eating including high cost, long commutes and poor quality of fresh foods ( 41 ) . Formative research for Pathways, a large, multi-site obesity prevention initiative in tribal communities, found that caregivers of schoolchildren reported driving considerable distances to shop at grocery or discount stores to acquire food for the family, due to reported poor availability of fresh fruits, vegetables and low-fat dairy at local reservation stores ( 31 ) . In a recent study conducted in another rural Northern Plains reservation, 40 % of households reported low food security ( 47 ) , reinforcing the need for environmental interventions to increase affordable nutrient-rich food choices on or near the reservation as well as individual-level dietary interventions.…”
Section: Discussionmentioning
confidence: 99%
“…As this method has successfully been used with children, adults and other AI tribal communities, it is considered well suited to identify and prioritize salient barriers and facilitators to DGA adherence faced by both children and adults (36)(37)(38) . Most individuals have a personal conceptualization of a 'healthy diet' (31,(39)(40)(41) . However, the low rates of DGA adherence indicate that most are unaware of the specifics of the DGA.…”
Section: Nominal Group Technique Methodsmentioning
confidence: 99%
See 1 more Smart Citation